Certificateless multi-replica public integrity auditing scheme for dynamic shared data in cloud storage. Issue 103 (April 2021) - Gudeme, Jaya Rao; Pasupuleti, Syam Kumar; Kandukuri, Ramesh
Abstract: Cloud storage enables data users to store and access their data anytime, from any location, using any device, under a pay-per-use policy. However, cloud storage raises various security concerns such as integrity and availability of data. To address these problems simultaneously, recently, several multi-replica integrity auditing schemes have been proposed in the literature. However, most of the existing schemes are designed based on either the public key infrastructure (PKI) or identity-based cryptography (IBC), which suffers from a big burden of certificate management or key escrow problems. In this paper, we propose a Certficateless Multi-Replica Dynamic Public Auditing Scheme for Shared data in cloud storage to solve these problems. Our scheme supports shared data dynamics through a novel data structure, namely, the replica version table. Further, our scheme also supports secure user revocation from the group. Through the security analysis, we prove that our scheme is provably secure against type I/II/III adversaries under the hardness assumption of the standard CDH and DL problems in the random oracle model (ROM). The performance and experimental evaluation show that our scheme is efficient and practical.